Knowledge and practice of polio vaccination among mothers of infants attending community health centre of northern Kerala - Kaithery, Nivya Noonhiyil; Kumaran, Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2018)
Background: Poliomyelitis is a highly infectious disease caused by polio virus which invades the nervous system causing irreversible total paralysis.The aim of the study is to assess the knowledge and practice of mothers regarding polio vaccination. Methods: It’s a descriptive type of study conducted in mothers of Infants who had attended Community health centre of Kannur district during a study period of 2 weeks (June 1 to June 14, 2017). Written consent was obtained from the mothers. Data was collected using a semi structured questionnaire with 3 sections -demographic details, knowledge and practice. Data was analyzed and the results are expressed in terms of frequency and percentage. Results: A total of 220 women were studied. Out of 220 mothers, 93.6% had satisfactory knowledge and 90.45% mothers had their child immunized up to age according to National Immunization Schedule. All of them were taking their children to government hospital for vaccination and their main source of knowledge were health workers. Conclusions: In the present study, majority of the mothers had attended immunization class and had satisfactory knowledge. In order to achieve 100% vaccination coverage, we have to emphasize more on awareness campaigns.